The Adoption of Planned Behavior and Push-Pull Theories: Predicting Woman's Engagement Self-Employed Modelling - Sijabat, Rauly; Darmi Astuti, Sih (KnE Social Sciences, 2024)
Behavioral theory states that the formation of certain behaviors does not happen suddenly. There are precursor factors that push this behavior. This study investigates how engaged self-employed behavior in women can be formed. Considering that self-employed research on women is still limited and the contradiction in the literature regarding the necessity of entrepreneurship factor as the pushing negative factor and the opportunity of entrepreneurship as the pulling positive factor, this study develops an empirical model that tests the necessity of entrepreneurship and the opportunity of entrepreneurship factors as the motivational factors that push the willingness and self-engagement in women. The research results show that individual personality can be either an opportunity or a necessity of entrepreneurship factor that pushes self-employed willingness. Meanwhile, the environmental barriers factor is the necessity of entrepreneurship factor and the individual socioeconomic is the opportunity of entrepreneurship factor. Keywords: engagement of self-employed, willingness of self-employed